EUROGIN 2014 roadmap: Differences in human papillomavirus infection natural history, transmission and human papillomavirus‐related cancer incidence by gender and anatomic site of infection. Issue 12 (26th July 2014) - Giuliano, Anna R.; Nyitray, Alan G.; Kreimer, Aimée R.; Pierce Campbell, Christine M.; Goodman, Marc T.; Sudenga, Staci L.; Monsonego, Joseph; Franceschi, Silvia
<x xml:space="preserve">Abstract</x> Human papillomaviruses (HPVs) cause cancer at multiple anatomic sites in men and women, including cervical, oropharyngeal, anal, vulvar and vaginal cancers in women and oropharyngeal, anal and penile cancers in men. In this EUROGIN 2014 roadmap, differences in HPV‐related cancer and infection burden by gender and anatomic site are reviewed. The proportion of cancers attributable to HPV varies by anatomic site, with nearly 100% of cervical, 88% of anal and <50% of lower genital tract and oropharyngeal cancers attributable to HPV, depending on world region and prevalence of tobacco use. Often, mirroring cancer incidence rates, HPV prevalence and infection natural history varies by gender and anatomic site of infection. Oral HPV infection is rare and significantly differs by gender; yet, HPV‐related cancer incidence at this site is several‐fold higher than at either the anal canal or the penile epithelium. HPV seroprevalence is significantly higher among women compared to men, likely explaining the differences in age‐specific HPV prevalence and incidence patterns observed by gender. Correspondingly, among heterosexual partners, HPV transmission appears higher from women to men. More research is needed to characterize HPV natural history at each anatomic site where HPV causes cancer in men and women, information that is critical to inform the basic science of HPV natural history and the development of future infection and cancer prevention efforts.